Global, Regional, and National Epidemiology of Vision Impairment due to Diabetic Retinopathy Among Working‐Age Population, 1990–2021 - Yang Meng; Yuan Liu; Runping Duan; Baoyi Liu; Zhuangling Lin; Yuan Ma; Lan Jiang; Zijian Qin; Tao Li (Journal of Diabetes)
ABSTRACT Background To evaluate the global, regional, and national trends of vision impairment associated with diabetic retinopathy (DR) in the working‐age population (20–65 years) from 1990 to 2021. Methods This was a population‐based analysis using data from the Global Burden of Disease Study 2021. Vision impairment was defined as low vision (Snellen visual acuity of < 6/18 to ≥ 3/60) and blindness (Snellen visual acuity of < 3/60 or central visual field < 10°). The burden of DR‐related vision impairment, that is, prevalence and years lived with disability (YLD), was analyzed by sex, age, location, and sociodemographic index (SDI). A Bayesian age‐period‐cohort analysis was employed to forecast the future burden up to 2035. Results From 1990 to 2021, the global prevalence rate and YLD rate of DR‐related vision impairment increased significantly. In 2021, 2.85 million prevalent cases and 250 117 YLDs were reported, representing 2.8‐fold and 3.0‐fold increases compared to 1990, respectively. South Asia and China were identified as the most severely burdened region and country in 2021, respectively. Throughout 1990–2021, females consistently bore a greater burden than males. In terms of SDI, the burden was predominantly concentrated in middle‐SDI countries. Predictive analysis suggests a continued increase in the number of patients and YLDs by 2035. Conclusions Globally, there has been a substantial increase in the burden of DR‐related vision impairment among working‐age individuals, with disparities observed in terms of sex, location, and SDI. Given the projected worsening of this burden, targeted interventions are needed to address this global health challenge.